Therapeutic potential of HIV-1 entry inhibitor peptidomimetics - Korie, Nneka PU; Tandoh, Kwesi Z; Kwofie, Samuel K (Experimental Biology and Medicine, 2021)
Human immunodeficiency virus 1 (HIV-1) infection remains a public health concern globally. Although great strides in the management of HIV-1 have been achieved, current highly active antiretroviral therapy is limited by multidrug resistance, prolonged use-related effects, and inability to purge the HIV-1 latent pool. Even though novel therapeutic options with HIV-1 broadly neutralizing antibodies (bNAbs) are being explored, the scalability of bNAbs is limited by economic cost of production and obligatory requirement for parenteral administration. However, these limitations can be addressed by antibody mimetics/peptidomimetics of HIV-1 bNAbs. In this review we discuss the limitations of HIV-1 bNAbs as HIV-1 entry inhibitors and explore the potential therapeutic use of antibody mimetics/peptidomimetics of HIV-1 entry inhibitors as an alternative for HIV-1 bNAbs. We highlight the reduced cost of production, high specificity, and oral bioavailability of peptidomimetics compared to bNAbs to demonstrate their suitability as candidates for novel HIV-1 therapy and conclude with some perspectives on future research toward HIV-1 novel drug discovery
Keywords: Human immunodeficiency virus 1; Human immunodeficiency virus; broadly neutralizing antibodies; antiretroviral therapy; peptidomimetics; entry inhibitors; HIV-1 novel drug discovery